Model Lean Six Sigma di Industri Farmasi - Rini Mulyani Sari; Evan Nugraha (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2018)
Indonesia is one of the countries in the ASEAN Economic Community (AEC). To boost competitiveness and benefit from changes in the global industrial system at revolutionary era, lean six sigma approach to production systems in the pharmaceutical industry was used. The goal is to analyze the existing conditions, user expectations, how to overcome the obstacles that occur and the formulation of strengthening strategies on the production system of soft capsule lines. The method used an explanatory case study of production systems in the pharmaceutical industry using lean six sigma approach. The results of the research are the existing conditions of the production system have not met expectations, user expectations systems are not well understood, the formulation to overcome the constraints that occur in the production system and the formulation of the strengthening pharmaceutical industry’s production system strategy using lean six sigma approach.